ASPEK-ASPEK KEDISIPLINAN PADA ANGGOTA SANGGAR SENI DAN BUDAYA INTAN MANUAH KOTA PALANGKA RAYA - May Camaro Putra; Fatthiya Azzahra; Rima Dwi Aprilliya; Shaffa Maryama Putri Karmita; Sulistiawati; Junita Irtiyah; Amelia Fenty; Nor Cholivah; Izza Najiha Salsabila; Safiah Ivy Anggita; Natalia saberina br ginting; Romiaty Romiaty; Susi Sukarningsi (STKIP Subang, 2026)
This study aims to identify the disciplinary aspects of the members of Sanggar Seni dan Budaya Intan Manuah in Palangka Raya City. The background problem concerns the varying levels of discipline among members, such as lateness and irregular participation in training activities. This research employed a quantitative descriptive method using percentage analysis. The instrument consisted of 33 statements distributed to 60 members, with 54 valid responses returned. The results show that members’ discipline levels are generally high across all measured aspects: (1) mental attitude aspect – 59.25% high and 40.74% moderate; (2) good understanding of behavioral rules – 79.62% high and 20.37% moderate; (3) attitude and behavior – 77.77% high and 22.22% moderate; and (4) responsibility aspect – 81.48% high and 18.51% moderate. No respondents were categorized as low in any aspect. Therefore, responsibility is the highest aspect, while mental attitude is the lowest. Overall, members’ discipline is classified as high and shows positive development, yet continuous coaching and exemplary leadership are needed to strengthen the mental attitude of the members.